Finding a way: Footprints in Time, the Longitudinal Study of Indigenous Children - McPeake, T; Skelton, F (My University, 2011)
Footprints in Time follows more than 1,600 Indigenous Australian children from 11 sites across urban, regional and remote Australia. The study has achieved a high retention rate of 86% for Wave 2 despite extensive design and implementation challenges. This presentation will provide an overview of the methodology and describe some of the innovative design features that make this a world leading study which invests in communities to improve data quality and contribute to better outcomes LSIC used a clustered sample design, which covered communities in remote, regional and urban groups. LSIC sites were chosen to reflect the range of living environments for Aboriginal and Torres Strait Islander people and to be near a major centre to maximise employment and networking opportunities. Where possible, existing community engagement relationships were built upon and in all sites local community members were employed to consult Elders about protocols and local issues. This helped with recruiting and is still a vital source of support for retaining families in the Study. Many survey items have been selected to capture strengths and resilience that provide a more balanced and positive picture of indigenous communities, while still collecting information on problems that exist. For example, children are asked how they cope with bullying and parents tell us about ways they cope with stress. Feedback products focus on the positives such as, 89% of children in the study had a birth weight within the expected range and proportionally more children are cleaning their teeth as they grow older. Considerable effort has gone into designing a range of products for different audiences to feedback results for each wave of data collected. Footprints in Time was designed to provide data as a public good to communities and for use by governments and researchers to improve outcomes for Aboriginal and Torres Strait Islander people. The data users have access to remarkable insights into what Aboriginal and Torres Strait Islander parents and carers say is important about their culture for growing up strong children and what parent’s aspire to for their children. The Footprints in Time methodology is focussed on positive and strong relationships between interviewers and families, to keep them involved over time in the longitudinal study so that they will contribute to positive community images and better community and child outcomes.
Keywords: Culture -- Indigenous; Children; Surveys and Survey Methodology; Culture; Surveys and Survey Methodology; Culture and language; Surveys and Survey Methodology; Culture; Children; Indigenous; Culture and identity; Culture, identity and language